Study of the Intrinsic Factors Determining the Near-Threshold Fatigue Crack Propagation Behavior of a High-Strength Titanium Alloy - Huan Wang; Yongqing Zhao; Ping Guo; Fei Qiang; Lei Zhang; Zhongli Qiao; Shewei Xin (Metals)
The resistance to near-threshold fatigue crack growth and its correlation with the microstructure of the Ti-5Al-3Mo-3V-2Zr-2Cr-1Nb-1Fe alloy were investigated. K-decreasing fatigue crack propagation rate tests were conducted on compact tension samples (ASTM standard) with a stress ratio R of 0.1 and a frequency of 15 HZ in a laboratory atmosphere. At a similar strength level of 1200 MPa, the sample with a fine basket-weave microstructure (F-BW) displayed the slowest near-threshold fatigue crack propagation rate compared with the samples with equiaxed (EM) and basket-weave (BW) microstructures. The fatigue threshold value (ΔKth) was 4.4 MPa·m1/2 for F-BW, 3.6 for BW, and 3.2 for EM. The fracture surfaces and crack profiles were observed by scanning electron microscopy (SEM) and electron backscatter diffraction (EBSD) to elucidate the mechanism of fatigue crack propagation in the near-threshold regime. The results revealed that the near-threshold crack growth in the three samples was primarily transgranular. The crack always propagated parallel to the crystal plane, with a high Schmid factor. In addition, the near-threshold fatigue crack growth behavior was synergistically affected by the crack tip plastic zone and crack bifurcation. The increased fatigue crack propagation resistance in F-BW was attributed to the better stress/strain compatibility and greater number of interface obstacles in the crack tip plastic zone.